2011
DOI: 10.1186/1741-7015-9-83
|View full text |Cite
|
Sign up to set email alerts
|

Treating frailty-a practical guide

Abstract: Frailty is a common syndrome that is associated with vulnerability to poor health outcomes. Frail older people have increased risk of morbidity, institutionalization and death, resulting in burden to individuals, their families, health care services and society. Assessment and treatment of the frail individual provide many challenges to clinicians working with older people. Despite frailty being increasingly recognized in the literature, there is a paucity of direct evidence to guide interventions to reduce fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
90
0
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 46 publications
2
90
0
15
Order By: Relevance
“…Studies have shown that functional losses can be reversed or minimized through approaches that modify living habits and training for ADLs and IADLs, with positive consequences for self-perception of health. 14,15,21,40,41,[43][44][45] It should also be noted that the presence or otherwise of a cognitive deficit should be taken into account when planning care actions, as this is an important parameter in overall geriatric assessment. 41,42,46 Recent studies have shown that, regardless of whether cognitive impairment is a cause or an effect, it is associated with frailty among the elderly.…”
Section: 4152122mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that functional losses can be reversed or minimized through approaches that modify living habits and training for ADLs and IADLs, with positive consequences for self-perception of health. 14,15,21,40,41,[43][44][45] It should also be noted that the presence or otherwise of a cognitive deficit should be taken into account when planning care actions, as this is an important parameter in overall geriatric assessment. 41,42,46 Recent studies have shown that, regardless of whether cognitive impairment is a cause or an effect, it is associated with frailty among the elderly.…”
Section: 4152122mentioning
confidence: 99%
“…14,15,21,40,41,[43][44][45] It should also be noted that the presence or otherwise of a cognitive deficit should be taken into account when planning care actions, as this is an important parameter in overall geriatric assessment. 41,42,46 Recent studies have shown that, regardless of whether cognitive impairment is a cause or an effect, it is associated with frailty among the elderly. 39,42 The large percentage of individuals (59.0%) with an MMSE score of either less than or equal to 19 among illiterate members of the study population or individuals with less than one year of education, or less than or equal to 23 among those with more than one year of education, suggests that cognitive decline may exist among this elderly population and that there is a need for additional neuropsychological assessment.…”
Section: 4152122mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent meta-analyses and summaries suggest, at best, modest and time-limited effects on survival, functional status, health care use and other important outcomes (1)(2)(3)(4)(5)(6)(7)(8)(9). Several important challenges that may contribute to limited program effectiveness, especially for outpatient programs, include engagement of primary care providers, convenient and accurate screening approaches to yield efficient targeting of high risk individuals, and capacity to implement management recommendations (10)(11)(12)(13)(14)(15). In addition, the actual content of assessments has varied widely, as have the balance of medical, social and functional issues addressed by the process.…”
mentioning
confidence: 99%
“…Frail elderly people have increased risk of falls, disability, hospitalization and death, resulting in burden to individuals, their families, health care services and society [1][2][3].…”
mentioning
confidence: 99%